A Cleaner Mining Method for Waste Tailings as Paste Materials to Goafs. (22nd October 2020) - Liu, Yuxi; Liu, Zhixiang; Li, Keming; Deng, Sijia; Dong, Longjun
Abstract : Underground mining is the primary method to obtain economically valuable minerals, but it usually brings a large number of goafs (mined-out voids) and large quantities of waste tailings. The gradual accumulation of mine tailings has attracted worldwide attention because of its occupation and acidification of land, and a large number of goafs often lead to stope instability and ground subsidence. To solve the waste tailing accumulation and ground subsidence, a cleaner mining method—cemented tailing backfilling (CTB)—for filling mining goafs by tailings was proposed. Firstly, the volume of the goafs was detected, and the hydraulic-mechanical coupling properties of the original tailings were tested. Then, a reasonable mix proportion of tailings, binder, and water was determined based on laboratory experiments. Finally, the filling pipe network and filling system were designed according to the actual situation of the mine. This paper provides an environmental and economic method for treating tailing accumulation and preventing ground subsidence. At the same time, it was demonstrated in Linglong Gold Mine (LLGM), and a plan which allows 15.8 service years of nondischarge of tailings was designed in LLGM.